Efforts To Increase Revenue at CV. Citra Cemerlang - Hendra Kurniawan; Wulandari Harjanti; Sri Rahayu (Sean Institute, 2026)
The problems selected and discussed in this thesis are: Efforts to increase Revenue of CV. Citra Cemerlang, so the purpose of the situation from CV. Citra Cemerlang, is to increase revenue from Rp.383,211. 950,- in 2021 to Rp.1,029,161,295,- in 2024. Research carried out in CV. Citra Cemerlang, located in Jl, Sunan Drajat, No. 311 Lamongan, while time spent on research from January to March 2025. The research method used for this research is survey method and data collected through: 1) Documents analysis, 2) observation, and 3) the interview. Research instrument is a tool that will be used to analyze the function of the selected standard, are: a) Transaction Functions, b) Customer Seizing function, c) Marketing plan Function, d) production function, and e) Functions of Human Resource Management. Methods of data collection using the method of documentation. Internal and external factors analysis and their readiness indicators used to assess the readiness of 12 pre-defined Functions selected by using SWOT analysis. Alternative problem-solving steps starting from a function that has the lowest interest rate up to a function that has the highest interestrate.